2016
DOI: 10.21474/ijar01/488
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect on the Metabolism and Enzyme Activity in Some Harmful Insects.

Abstract: Effect of the magnetic field on the physiological aspects of some insects was studied for larvae of three insects reared in laboratory under 25 ±2°C and 70 ±5% RH in suitable rearing boxes. An experimental set-up was designed to measure the magnetic flux density in the rearing box. The magnetic field was calibrated to obtain the point of the maximum gradient. Magnetic flux density was measured using a Tesla meter and recorded average values of 21.8, 249 and 863 Gauss (G) for the 3 insects respectively. The thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The probability was 0.215. Hussein et al (2015) investigated the effect of magnetic field on the physiological aspects of some insects, larvae of three insects which cotton leafwarm, Spodoptera littoralis, red palm weevil, Rhynchophorus ferruginous and the greater wax moth, Galleria mellonella were rearing under laboratory condition.…”
Section: Resultsmentioning
confidence: 99%
“…The probability was 0.215. Hussein et al (2015) investigated the effect of magnetic field on the physiological aspects of some insects, larvae of three insects which cotton leafwarm, Spodoptera littoralis, red palm weevil, Rhynchophorus ferruginous and the greater wax moth, Galleria mellonella were rearing under laboratory condition.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review has evaluated the state of knowledge on the toxic effects of electromagnetic fields (EMF) on some insects [Thill, 2020]. Some general reviews have reported on the effects and mechanisms of EMF exposure on insects [Hussein et al, 2015], new findings in the cell biochemistry of insects, and the impact of changes in insects' biology or population dynamics [Kandil et al, 2018, 2019]. Additional negative effects that were described in different studies included the direct exposure of adult Pectinophora gossypiella and E. insulana to magnetic power (42, 12, and 4.2 mT), showing that some biological aspects were affected, such as development time, malformation of different stages, and generation times [Said et al, 2017; Kandil et al, 2018, 2019], along with reduced reproductive ability and fertility [Balmori, 2015], lethargy, failure to find food, escape behavior, disturbance of the sense of orientation, and reduced reaction speed.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has evaluated the state of knowledge on the toxic effects of electromagnetic fields (EMF) on some insects [Thill, 2020]. Some general reviews have reported on the effects and mechanisms of EMF exposure on insects [Hussein et al, 2015], new findings in the cell biochemistry of insects, and the impact of changes in insects' biology or population dynamics [Kandil et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetism and using magnetic field seems to be promising physical method in pest control (Hussein et al, 2014). Recently we have to focus some lights on magnetism and the effect of electro-magnetic waves on the different biological aspects of insects.…”
Section: Introductionmentioning
confidence: 99%
“…temperature, different types of waves e.g. gamma rays (Hussein et al, 1999) and electro-magnetic waves (Hussein et al, 2014). Sak et al (2011) in their studies on Galleria mellonella larvae stated that total protein increase in cases of injury and wounding or exposure to high doses of venoms.…”
Section: Introductionmentioning
confidence: 99%